Mini-Craniotomy for Chronic Subdural Hematoma: A Reliable Surgical Option - Rao, Gollapudi Prakash; Imran, Mohammed; Raju, Reddycherla Naga; Sandeep, Pittala; Reddy, Kotha Arjun (Asian Journal of Neurosurgery, 2024)
Introduction Chronic subdural hematoma (SDH) is one of the most common conditions encountered in the neurosurgical practice. Surgical modalities like twist drill craniostomy, burr hole evacuation, mini-craniotomy, and craniotomy are practiced in the management of chronic SDH. Mini-craniotomy without excision of membranes may help to achieve best results with decreased complication rate.Materials and Methods Patients with chronic SDH operated from September 2013 to September 2022 were included in the study. Mini-craniotomy (40–60 mm) was done and cruciate incision was given over the dura. Dura was left wide open by reflecting and suturing the cut edges of the dural leaflets to the craniotomy edge allowing to evacuate subdural space under vision during surgery and to allow any residual collection to drain out freely in the postoperative period. A drain was placed between the inner membrane and the bone flap. Preoperative and postoperative clinical and radiological parameters were recorded. Complications, recurrence, and residual collections were noted.Results Seventy-seven patients were included in the study. Mean age was 57.32 years. Median Glasgow Coma Scale (GCS) at presentation was 13 while median GCS at discharge was 15. Two patients with preexisting comorbidities expired after surgery due to medical causes. No recurrences were noted. Fourteen patients had residual collections which resolved by 6 weeks. Two patients had wound infection. One of these patients later needed a bone flap removal due to osteomyelitis.Conclusion Mini-craniotomy without membranectomy is a good option for complete evacuation of chronic SDH under vision mainly avoiding the complication of membranectomy. It is not associated with increased complications rate. It needs fewer follow-ups as brain expansion can be established radiologically in a short period.
Keywords: chronic subdural hematoma; mini craniotomy; membranectomy; residual collections; recurrence